Solitary Abdominal Wall Lymph Node Recurrence in Prostate Cancer Patient with Dramatic Prostate-Specific Antigen Decrease following Metastasectomy. (10th February 2023) - Williams, Andrew; Elbakry, Amr A.; Trump, Tyler; Prisneac, Ion; Smolkin, Matthew; Zekan, David; Salkini, Mohamad W.
Abstract : Prostate cancer patients routinely undergo surveillance for recurrence using prostate-specific antigen (PSA). While PSA's benefit in screening is controversial, its use for detecting recurrence in patients with history of prostate cancer is pivotal. Rising PSAs with the newly advanced prostate-specific membrane antigen positron emission tomography (PSMA PET) can help localize the location of recurrences for better excision and management. Here, we present a 55-year-old with prostate cancer, with initially undetectable postprostatectomy PSA levels, who later presented with a PSA of 3.47 ng/mL. PSMA PET showed isolated uptake in an abdominal wall mass. Pelvic lymphadenectomy and abdominal wall mass excision were performed, confirming a single metastasis in an abdominal wall lymph node. Metastasectomy led to a dramatic drop in PSA to 0.10 ng/mL both postoperatively and on long-term follow-up. Our case illustrates the potential benefit of metastasis-directed therapy in delayed oligometastasis following definitive management of prostate cancer.